Penanggulangan Maraknya Angka Pernikahan Dini - Wa Ode Rahayu; Elsa Natasary; Nining Aria; Selvi Nezalasmi; Citra Prasiska Puspita Tohamba (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Early marriage is a marriage that takes place when entering adolescence, not yet adolescence, or just ending adolescence. In Indonesia itself, although the law strongly opposes early marriage, this case often increases every year. Apart from the inherent traditional factors, parental coercion, economic and social factors or even worse, the factor of getting pregnant outside of marriage is often the reason why early marriages are carried out.